A Reexamination of Exchange-Rate Exposure - Dominguez, Kathryn M. E; Tesar, Linda L (American Economic Review, 2001)
Finance theory suggests that changes in exchange rates should have little influence on asset prices in a world with integrated capital markets. Indeed, the existing literature examining the relationship between international stock prices and exchange rates finds little evidence of systematic exchange rate exposure. We argue in this paper that the absence of evidence may be due to restrictions imposed on the sample of data and the empirical specifications used in previous studies. We study a broad sample of firms in eight countries over an eighteen-year period. We find that firm-level and industry-level share values are significantly influenced by exchange rates. Further, we do not find evidence that exchange rate exposure is falling (or becoming less statistically significant) over time. Our results suggest that significant firm, industry and country-specific differences remain even as financial markets become more and more integrated.